2000
DOI: 10.1021/ac991005l
|View full text |Cite
|
Sign up to set email alerts
|

High Extraction Efficiency for POPs in Real Contaminated Soil Samples Using Accelerated Solvent Extraction

Abstract: Systematic investigations were performed to study the dependence of the extraction efficiency of persistent organic pollutants (POPs), including chlorobenzenes, HCH isomers, DDX, PCB congeners, and PAHs, on the accelerated solvent extraction (ASE) operating variables solvent and temperature. Mixed soil samples from two locations with considerable differences in soil properties and contamination in the Leipzig-Halle region (Germany) were used. The objective was to optimize ASE for the extraction of POPs from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 18 publications
3
55
0
2
Order By: Relevance
“…4 shows that PCBs removal efficiency was not obvious at lower temperatures (90-110 • C), and it continuously increased till around 150 • C, but declined at higher temperature 170 • C for congeners of PCB66, PCB118, PCB153, PCB138, PCB180 and PCB170. This implied that desorption of PCBs from sample matrix controls the removal efficiency [39] and certain intermolecular bonds between PCBs and soil matrix can only be broken at higher temperatures and pressures, and this is probably the decisive advantage of solvothermal procedure as compared to Soxhlet or elution [40]. However, certain temperature range (>150 • C) may limit the removal efficiency, as also demonstrated by Hubert et al [40].…”
Section: Optimization Of the Solvothermal Proceduresmentioning
confidence: 87%
See 1 more Smart Citation
“…4 shows that PCBs removal efficiency was not obvious at lower temperatures (90-110 • C), and it continuously increased till around 150 • C, but declined at higher temperature 170 • C for congeners of PCB66, PCB118, PCB153, PCB138, PCB180 and PCB170. This implied that desorption of PCBs from sample matrix controls the removal efficiency [39] and certain intermolecular bonds between PCBs and soil matrix can only be broken at higher temperatures and pressures, and this is probably the decisive advantage of solvothermal procedure as compared to Soxhlet or elution [40]. However, certain temperature range (>150 • C) may limit the removal efficiency, as also demonstrated by Hubert et al [40].…”
Section: Optimization Of the Solvothermal Proceduresmentioning
confidence: 87%
“…This implied that desorption of PCBs from sample matrix controls the removal efficiency [39] and certain intermolecular bonds between PCBs and soil matrix can only be broken at higher temperatures and pressures, and this is probably the decisive advantage of solvothermal procedure as compared to Soxhlet or elution [40]. However, certain temperature range (>150 • C) may limit the removal efficiency, as also demonstrated by Hubert et al [40]. In contrast, concentrations of PCB8, PCB18, PCB28 and PCB44 kept increase from 90 • C to 170 • C. The difference in optimal temperatures for PCB congeners was ascribed to the different chlorination degree of PCB congeners as discussed by Björklund et al [20].…”
Section: Optimization Of the Solvothermal Proceduresmentioning
confidence: 99%
“…It allows the universal use of solvents or solvent mixtures with different polarities and individually variable pressures of 5-200 atm (0.3-20 MPa) in order to maintain the extraction solvent in a liquid state, and temperatures ranging from room temperature up to 200°C in order to accelerate extraction. The solvent volume can be reduced because the solubility increases 74 . The use of ASE in the analysis of residual pesticides in food has been reported by a few researchers.…”
Section: 8-accelerated Solvent Extraction (Ase)mentioning
confidence: 99%
“…It was reported that nonextracted atrazine, isoproturon, and dicamba residues in several soils could be absorbed to earthworm tissues [34]. It was also found that a considerable fraction of nonextractable PAH residues in a soil could be mineralized under different ecological stress conditions [35]. Although many investigators now pursue less aggressive extraction techniques to approximate or mimic bioavailability, how the different extraction methods are related to the bioavailability of APs in the sediments is our future research goal.…”
Section: Environmental Implicationmentioning
confidence: 99%
“…Some studies have made a comparison between ASE and Soxhlet extraction and found that the performance of ASE was consistently equivalent to or better than Soxhlet extraction [35,36]. The ASE (Dionex 300, USA) is an automated system for extracting organic compounds from a variety of solid samples.…”
Section: Ase Extractionmentioning
confidence: 99%